Making Choices and Reducing Risk (MCARR): School Counseling Primary Prevention of Substance Use - Foss-Kelly, Louisa L.; Generali, Margaret M.; Crowley, Michael J. (Professional Counselor, 2021)
The consequences of adolescent drug and alcohol use may be serious and far-reaching, forecasting problematic use or addictive behaviors into adulthood. School counselors are particularly well suited to understand the needs of the school community and to seamlessly deliver sustainable substance use prevention. This pilot study with 46 ninth-grade students investigates the impact of the Making Choices and Reducing Risk (MCARR) program, a drug and alcohol use prevention program for the school setting. The MCARR curriculum addresses general knowledge of substances and their related risks, methods for evaluating risk, and skills for avoiding or coping with drug and alcohol use. Using a motivational interviewing framework, MCARR empowers students to choose freely how they wish to behave in relation to drugs and alcohol and to contribute to the health of others in the school community. The authors hypothesized that the implementation of the MCARR curriculum would influence student attitudes, knowledge, and use of substances. Results suggest that the MCARR had a beneficial impact on student attitudes and knowledge. Further, no appreciable increases in substance use during the program were observed. Initial results point to the promise of program feasibility and further research with larger samples including assessment of longitudinal impact.
0 citations (Crossref) [2023-10-31] ERIC Number: EJ1312406
Keywords: Adolescents; Counselor Role; Decision Making; Grade 9; Health Behavior; High School Students; Knowledge Level; Prevention; Program Effectiveness; Risk; School Counseling; School Counselors; Student Attitudes; Substance Abuse; Urban Schools; dept.csp; peer-reviewed

School Counseling Programs Identifying Academic Development Needs - Parzych, Jennifer L.; Generali, Margaret; Yavuz, Olcay (Journal of Education, 2021)
This study examined student, parent, and faculty perceptions of academic development needs and related comprehensive school counseling program services from four urban middle and high schools. Participants (n = 1,032) completed a survey designed to assist schools in planning and evaluating their career and college readiness programs, and exploring perceived student support needs. Statistically significant differences were observed in stakeholder perceptions among 12 identified interventions that support improved academic development, through factorial analysis of variance (ANOVA) and pairwise comparisons analysis. Findings provide valuable information about prioritizing student academic counseling services strategically and effectively, to meet program needs of students in high-poverty schools.
1 citations (Crossref) [2023-10-31]
Keywords: academic development; college readiness; dept.csp; dept.edl; peer-reviewed; poverty; school counselors